A importância da OMC para o desenvolvimento do comércio numa economia globalizada - Graziano, Gabriel Kubik (2018)
This paper aims to analyze and understand the beginning of the process of trade liberalization that started in the 1990s which was considered the boom of globalization into the historical events that occurred in that period. Understand how the trade liberalization was intensified by the consequences of globalization and how the World Trade Organization has been working to support and defend legal trade practices. The WTO must act in this direction, reducing borders and developing greater capacity for cooperation between different governments. The research seeks to show the organization's guidelines for achieving the elements that govern the globalization process, the WTO as an agent and the trade liberalization as a result of this relationship. The globalization process has its positive and negative points that will be raised in order to justify that globalization is a partner of the WTO in the international trading system. The Rare Earth question is better observed in mining sector, those minerals have a high price and ended up in comercial problem involving different countries where the OMC act efficiently.